2021
DOI: 10.3389/fimmu.2021.744696
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Inpatient Mortality Associated With Nosocomial and Community COVID-19 Exposes the Vulnerability of Immunosuppressed Adults

Abstract: BackgroundLittle is known about the mortality of hospital-acquired (nosocomial) COVID-19 infection globally. We investigated the risk of mortality and critical care admission in hospitalised adults with nosocomial COVID-19, relative to adults requiring hospitalisation due to community-acquired infection.MethodsWe systematically reviewed the peer-reviewed and pre-print literature from 1/1/2020 to 9/2/2021 without language restriction for studies reporting outcomes of nosocomial and community-acquired COVID-19. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 68 publications
2
46
0
2
Order By: Relevance
“…Overall, our analyses suggest that part of these in-hospital mortality risk reductions could be sustained if hospital capacity is maintained and hospital-acquired infections are prevented. These findings are aligned with those from studies conducted worldwide 14,25,40-42 . Limited critical care resources and rapidly increasing staff-to-patient ratio could have influenced patient outcomes during periods of high transmission 29,43 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Overall, our analyses suggest that part of these in-hospital mortality risk reductions could be sustained if hospital capacity is maintained and hospital-acquired infections are prevented. These findings are aligned with those from studies conducted worldwide 14,25,40-42 . Limited critical care resources and rapidly increasing staff-to-patient ratio could have influenced patient outcomes during periods of high transmission 29,43 .…”
Section: Discussionsupporting
confidence: 87%
“…Limited critical care resources and rapidly increasing staff-to-patient ratio could have influenced patient outcomes during periods of high transmission 29,43 . Additionally, nosocomial infections could exacerbate mortality risk because the already admitted patient population has vulnerable health conditions and higher rates of comorbidities 42,44 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have confirmed that immunocompromised patients are at high risk of developing severe COVID-19 disease and of dying when infected with SARS-CoV-2 (65)(66)(67)(68). This seems to be particularly the case in patients with combined defects of B and T cell immunity as observed early after transplantation as well as in patients given intensive chemotherapy (69)(70)(71)(72)(73).…”
Section: Immune Response To Sars-cov-2 Mrna Vaccination In Immunocomp...mentioning
confidence: 93%
“…Throughout the pandemic, nosocomial transmission of SARS-CoV-2 has been a major concern [5] , with hospital-acquired infections (HAIs) accounting for more than 5% of lab-confirmed cases from March-August 2020 in the UK [6] and representing 11% of COVID-19 cases within hospitals in this period [7] . HAIs also frequently occur within a very vulnerable population with high levels of mortality [6, 8, 9] . There is therefore an unmet need to develop interventions that can reduce the occurrence of nosocomial transmission.…”
Section: Introductionmentioning
confidence: 99%